Heart Rate Variability Biofeedback Based on Slow-Paced Breathing With Immersive Virtual Reality Nature Scenery - Blum, Johannes; Rockstroh, Christoph; Göritz, Anja S. (Frontiers in Psychology, 2019)
This study investigated the benefits of using a virtual nature environment to administer immersive heart rate variability biofeedback (HRV-BF) based on slow-paced breathing. We compared the Virtual Reality (VR)-based HRV-BF with a standard implementation in a randomized controlled experiment with 60 healthy employees. After a cognitive stress induction, the participants performed a single-session of HRV-BF before repeating the cognitive stressor task. VR-based versus standard HRV-BF were comparable in terms of biofeedback performance (cardiac coherence and cardiac vagal tone). However, the VR-based implementation buffered perceived stress in the subsequent stressor task, increased relaxation self-efficacy more, reduced mind wandering, helped participants focus on the present moment, and helped preserve attentional resources. Potential long-term effects and generalizability need to be assessed in future research.